WHOSE VOICE Is That? - Mohd. Khairul Azman Ismail, 1975-; Nur Azira Natasha Zulkipli; Nusaybah Maszlee; Ainnur Amani Rozahani (Cyberjaya, Selangor : KAWANDANET SDN. BHD., 2023)
WHOSE VOICE IS THAT? is a picture book that explores friendship, love and the creatures that are typically found in a village.
Keywords: Children's stories, English; Malaysian fiction (English)